PROSPECTS OF CLINICAL USE OF OFLOXACIN IN GYNECOLOGY AND UROLOGY - A. A. Khryanin; O. V. Reshetnikov (Антибиотики и Химиотерапия)
The review provides the present Russian and international data on the effectiveness of ofloxacin. The drug is effective and safe in the treatment of various pathologies. The drug is sufficiently effective and safe in the treatment of the urological and gynecological infectious pathologies.